Pladsgaranti - men ingen garanti for indholdet. Børns dagpasning i Danmark 1960-1996 - Thorsen, Hanne (Kvinder, Køn & Forskning, 1997)
Denmark has the most developed public day care service in the world. The day care system is the daily condition of 281.076 children in the age group 0-5. The Nurshing of children is a timeressource that women purchase from the Welfare State institutions, and at the same time an instrument of the labour-marked which create the basis for the high workforce participation of Danish women. The ongoing subject for public discussion has been the waiting list problem. How does local councils provide room enough for the children without raising the public spendings. Surprisingly the discussion of the pedagogical contents has played a secondary role. The article ends up by recommending a serious discussion of the pedagogical aims and contents, in order to qualify the children to cope with a changing society.